South East Asian (SEA) Games biomechanics project - Wei, X.; Teh, K. C.; Raynor, A. J. (1998)
The 19th SEA Games were held in Jakarta, Indonesia in October 1997 and presented an ideal opportunity for much needed kinematic data to be collected from the track and field athletes representing the ten South East Asian countries. The quantitative data obtained from high speed video cameras will be used to provide coaches and athletes with information to further improve their performance.